2014
DOI: 10.1371/journal.pone.0096481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Efficacy of Topically Applied Nonsteroidal Anti-Inflammatory Drugs in Retinochoroidal Tissues in Rabbits

Abstract: PurposeTo evaluate the pharmacokinetics and efficacy of topically applied nonsteroidal anti-inflammatory drugs (NSAIDs) in the retinochoroidal tissues of rabbits.MethodsThe cyclooxygenase (COX) inhibitory activity of diclofenac, bromfenac, and amfenac, an active metabolite of nepafenac, were determined using human-derived COX-1 and COX-2. Each of the three NSAIDs was applied topically to rabbits, and after 0.5 to 8 hrs, the concentration of each drug in the aqueous humor and the retinochoroidal tissues was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 40 publications
1
38
0
7
Order By: Relevance
“…It also increases the drug's potency against COX-1 and COX-2 compared with amfenac [9]. For instance, the half maximal inhibitory concentrations of bromfenac, amfenac and diclofenac were 5.56, 15.3 and 55.5 nM, respectively, for human-derived COX-1 and 7.45, 20.4 and 30.7 nM, respectively, for human-derived COX-2 [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also increases the drug's potency against COX-1 and COX-2 compared with amfenac [9]. For instance, the half maximal inhibitory concentrations of bromfenac, amfenac and diclofenac were 5.56, 15.3 and 55.5 nM, respectively, for human-derived COX-1 and 7.45, 20.4 and 30.7 nM, respectively, for human-derived COX-2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism of action is believed to result from its potent (in the nM range) inhibitory effect on cyclooxygenase (COX)-1 and -2 and, thus, on prostaglandin synthesis [7,9]. The presence of bromine in the bromfenac molecule increases the lipophilicity of bromfenac, with the drug being more lipophilic than amfenac (another NSAID) [partition coefficient (log P) of 2.23 vs. 1.23] [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In rabbits, topical bromfenac reaches the vitreous and retinochoriodal tissues, and after a single topical administration is detectable in the retinochoroid up to 24 hours. 8,17,18 Kida et al 19 showed that compared to nepafenac and diclofenac, bromfenac concentration after topical application on rabbit eyes was continuously higher in the retinochoroidal tissues. Thus, bromfenac may have a better therapeutic effect than these two other NSAIDs in retinochoroidal inflammatory diseases.…”
mentioning
confidence: 99%
“…37 Bromfenac and nepafenac are NSAIDs that have excellent corneal and sclera penetration and have both been shown to reach the retina in therapeutic doses in animals, 38,39 although bromfenac would appear to be superior. 40 Recently, there has been interest in using bromfenac, ketorolac, and other NSAIDs as an adjunct to anti-VEGF drugs or intravitreal steroids 41 for macular edema from DME, RVO, 42 uveitis, 41 and also choroidal neovascularization (CNV), as there is evidence that COX plays an important role in promoting angiogenesis in CNV. 50 Nakano and others have demonstrated that steroid eye drops (difluprednate ophthalmic emulsion) can be effective in reducing retinal thickness in eyes with DME, in eyes that have been vitrectomized, 51 and in eyes prior to vitrectomy.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%